2003
DOI: 10.1081/bio-120025409
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Alginates for Grafting: Impact of Alginate Molecular Weight

Abstract: Optimising microencapsulation technology towards the effective clinical transplantation has created the need for highly biocompatible alginates. Therefore, in this study the biocompatibility of different beads prepared from alginates with varying average molecular weight was examined. In some experiments the beads were covered with a multilayer membrane surrounded by an alginate layer. First of all, we found that beads made of a lower weight average alginate elicted a much stronger fibrotic response compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Zhang and co‐workers have determined the degree of FO by measuring the thickness of the pericapsular fibrotic layer, as indicated by Goldner staining 23, 24. Similarly, Schneider et al have adopted the fibrotic area per capsule (in μm2) to indicate the severity of fibrotic reaction 25. In addition, other parameters, such as the retrieval rate of microcapsules and the percentage of microcapsules with overgrowth, served as indexes of severity of FO 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and co‐workers have determined the degree of FO by measuring the thickness of the pericapsular fibrotic layer, as indicated by Goldner staining 23, 24. Similarly, Schneider et al have adopted the fibrotic area per capsule (in μm2) to indicate the severity of fibrotic reaction 25. In addition, other parameters, such as the retrieval rate of microcapsules and the percentage of microcapsules with overgrowth, served as indexes of severity of FO 26…”
Section: Discussionmentioning
confidence: 99%
“…Schneider utilized Photoshop software for objective quantification of FO, and fibrotic area per capsule was served as one index of severity of FO;25 however, the method was time‐consuming, because it manually processed only one image at a time and was impossible to process in batches. In the present study, a macro was created with the use of Image‐Pro Plus software.…”
Section: Discussionmentioning
confidence: 99%
“…The abdomen was sutured and the animals were checked daily for blood glucose concentrations. Explanted microcapsules were evaluated for fibrotic overgrowth under a Wilowert S microscope (Hund GMBH, Wetzlar, Germany), as previously described (21). Images were captured with a digital camera and stored as jpg files.…”
Section: Methodsmentioning
confidence: 99%
“…It was also reported that molecular weight may influence the in vitro and in vivo response to alginate gel and capsules [21]. So we observed the purification process induces a change in the viscosity-average molecular weight of alginate.…”
Section: Resultsmentioning
confidence: 73%